2021
DOI: 10.1021/jacs.1c04261
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed γ,γ′-Diarylation of Free Alkenyl Amines

Abstract: The direct difunctionalization of alkenes is an effective way to construct multiple C–C bonds in one-pot using a single functional group. The regioselective dicarbofunctionalization of alkenes is therefore an important area of research to rapidly obtain complex organic molecules. Herein, we report a palladium-catalyzed γ,γ′-diarylation of free alkenyl amines through interrupted chain walking for the synthesis of Z-selective alkenyl amines. Notably, while 1,3-dicarbofunctionalization of allyl groups is well pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 91 publications
2
9
1
Order By: Relevance
“…Following this, the same group extended to report the efficient synthesis of Z -selective alkenyl amines by the γ,γ′-diarylation reaction of unprotected β-alkyl allylamines through an interrupted chain walking process (Scheme ). In this case, they found that the choice of silver salt plays a significant role in arylating the less bulkier secondary and tertiary amines. Even the unprotected allyamines could react efficiently in this protocol.…”
Section: Alkenyl C–h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…Following this, the same group extended to report the efficient synthesis of Z -selective alkenyl amines by the γ,γ′-diarylation reaction of unprotected β-alkyl allylamines through an interrupted chain walking process (Scheme ). In this case, they found that the choice of silver salt plays a significant role in arylating the less bulkier secondary and tertiary amines. Even the unprotected allyamines could react efficiently in this protocol.…”
Section: Alkenyl C–h Bond Functionalization Of Aliphatic Alkenes Cont...mentioning
confidence: 99%
“…= 1:3) meant the possibility of a regioselectivity switch to allylic products. Encouraged by this hypothesis, more nonpolar solvents were tested (entries [18][19], and the r.r. value could be elevated to 1:8 in benzene with a low overall yield of 15% for the coupling products.…”
Section: Screening Of the Reaction Conditionsmentioning
confidence: 99%
“…In the past few decades, unremitting efforts have been devoted to this field 11,12 . White et al pioneered a substrate-chelated oxidative Heck reaction of phenylboronic acids and unactivated alkenes tethered with proximal heteroatoms for the regioselective synthesis of vinyl products [13][14][15][16][17][18] . Shortly thereafter, the Sigman group reported a catalyst-controlled β-H elimination process in both oxidative and classic Heck reactions of unactivated alkenes, giving good selectivity for the E-styrenyl products.…”
mentioning
confidence: 99%
“…In the meantime, the leverage of the M–H intermediate as the reactive intermediate through the chain-walking strategy has recently been the focus of efforts toward the remote functionalization of alkenes. Notable examples include the asymmetric Pd-catalyzed relay-Heck reaction, and the migratory asymmetric hydrofunctionalization of olefins involving an NiH intermediate. These approaches enable facile access to one distal stereogenic center from the functional group. In stark contrast, the migratory asymmetric dicarbofunctionalization of acyclic internal alkenes has remained underdeveloped. If realized, the concomitant formation of the incontiguous stereocenters would enable the expedient synthesis of chiral acyclic organic molecules that is challenging for the traditional synthetic routes. At the outset of this project, we envisioned that the judicious choice of alkene bearing a mono-coordinated group would offer the opportunity to control the regio- and diastereoselectivity, while the interception with a wide range of bidentate chiral ligands would result in high enantioselectivity. , To this end, we report the progress on the asymmetric Pd-catalyzed diarylation of internal acyclic alkenes by the reaction of diazonium salts, organoboronic reagents, and two types of easily accessible internal alkenes, allyl carbamates, and enamides (Figure c).…”
Section: Introductionmentioning
confidence: 99%